Bank Capital Adequacy in Australia - Sheridan, Niamh (IMF Working Papers; Working Paper ;, 2012)
The paper finds that, given Australia's conservative approach in implementing the Basel II framework, Australian banks' headline capital ratios underestimate their capital strengths. Given their high capital quality and the progress in their funding profiles since the global financial crisis, the Australian banks are making good progress toward meeting the Basel III requirements, including the new liquidity standards. Stress tests calibrated on the Irish crisis experience show that the banks could withstand sizable shocks to their exposure to residential mortgages. However, combining residential mortgage shocks with corporate losses expected at the peak of the global financial crisis would put more pressure on Australian banks' capital. Therefore, it would be useful to consider the merits of higher capital requirements for systemically important domestic banks.